BO‘LAJAK PEDAGOGLARNI KASBIY SHAKLLANTIRISHDA TASVIRIY SAN’ATNING NAZARIY MASHG‘ULOTLARNI TASHKIL ETISH METODIKASI - Baymetov, B.B. (SCIENCE and SOCIETY, 2023)
The article fosuses on aimed at organizing theoretical classes in the preparation of highly qualified teachers in the field of fine arts. It also describes the statements of great scientists in the field of fine arts, ancient artists, devoted to the theoretical issues of fine arts.
Keywords: fine arts; drawing; painting; composition; methodology; professional qualification; artistic creativity